Doświadczenie macierzyństwa w XIX wieku - Szablińska, Joanna (Karkonoska Państwowa Szkoła Wyższa, 2011)
This work is an attempt of reconstruction of a motherhood pattern in XIX century. Two models of women have been taken into consideration, namely woman as a housewife and as a mother. In order to reconstruct these models, it was planned to use knowledge written down in XIX century guide literature. Through analisys of chosen group of guide books, state of social consciousness and some generalization of universal phenomena were examined. Ali common advice connected with the aspects of raising children were also noticed and mentioned in this report.
Keywords: macierzyństwo; rodzina; 19 w.; wychowanie